2022
DOI: 10.1155/2022/9141117
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Prognostic Model Based on Pyroptosis-Related Genes in Pancreatic Adenocarcinoma

Abstract: Background. The importance of pyroptosis in tumorigenesis and cancer progression is becoming increasingly apparent. However, the efficacy of using pyroptosis-related genes (PRGs) in predicting the prognosis of pancreatic adenocarcinoma (PAAD) patients is unknown. Methods. This investigation used two databases to obtain expression data for PAAD patients. Differentially expressed PRGs (DEPRGs) were identified between PAAD and control samples. Several bioinformatic approaches were used to analyze the biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Furthermore, Su et al reported the high prognostic performance of pyroptosis-related genes ( GSDMC , IRF1 , and PLCG1 ). They found that this model performed well in predicting the 1-, 3- and 5-year survival of TCGA-PAAD patients [ 43 ]. Despite this, our model demonstrates good predictive value in general, and we are the first to examine EALMRG signatures in PAAD prognosis prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Su et al reported the high prognostic performance of pyroptosis-related genes ( GSDMC , IRF1 , and PLCG1 ). They found that this model performed well in predicting the 1-, 3- and 5-year survival of TCGA-PAAD patients [ 43 ]. Despite this, our model demonstrates good predictive value in general, and we are the first to examine EALMRG signatures in PAAD prognosis prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in tumor immunity varies depending on the organ and tissue context ( 63 ). Initially, abnormal up-regulation of GSDMC is identified in metastatic melanoma, earning it the label of melanoma-derived leucine zipper extra-nuclear factor (MLZE) and making it a molecular beacon for tracking melanoma evolution ( 27 , 65 ).…”
Section: The Expression Of Gsdm and Clinical Significance In Tumor Im...mentioning
confidence: 99%
“…Moreover, GSDMC undergoes hypomethylation in LUAD cells, and elevated levels usually hint at a grim prognosis for LUAD patients ( 63 ). In pancreatic cancer, GSDMC’s presence is nearly double compared to healthy tissues, correlating with reduced patient longevity ( 65 , 129 ). Research led by Yun-Qian Cui indicates pronounced expression of GSDMC in ccRCC, linking it to adverse survival rates ( 54 ).…”
Section: The Expression Of Gsdm and Clinical Significance In Tumor Im...mentioning
confidence: 99%
“…GSDMC can be used as an additional predictive factor for hepatocellular carcinoma ( 64 ). Furthermore, the expression levels of mouse GSDMC are positively correlated with the metastatic ability of B16 melanoma cell lines ( 65 ). However, knockdown of GSMDC attenuates the proliferation of colorectal cancer cell lines ( 66 ).…”
Section: Inflammasome-mediated Pyroptosismentioning
confidence: 99%